Harmonizing Imagination and Technology: Emmas Fröhlicher Tag-A Fusion of Printed Picture German Storybook and Digital Web Experience on Google Sites - Pratama, Kisma Bagus; Aini, Desti Nur; Yusuf, Robe'ah (Nexus Publishing NXP, 2024)
This study aims to develop a hybrid educational tool, combining a printed picture German storybook with a digital web experience, to assess the effectiveness of the hybrid tool in enhancing German language learning for beginners, specifically focusing on language acquisition and imaginative skills. This research adopts the Research and Development (R&D) approach, employing the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. The study involves the creation of